Validity of aerobic capacity indicators derived from the progressive specific taekwondo test for prescribing sport-specific interval training - Apollaro, Gennaro; Panascì, Marco; Ouergui, Ibrahim; Franchini, Emerson; Ruggeri, Piero; Falcó, Coral; Faelli, Emanuela (Frontiers in Physiology, 2025)
BackgroundThe Progressive Specific Taekwondo Test (PSTT) is used to determine indicators of aerobic capacity (heart rate deflection point [HRDP] and kick frequency at the HRDP [KFDP]) useful for prescribing sport-specific training. The aim of this study was to prescribe a sport-specific interval training (IT) session at the KFDP, identified during the PSTT, and to investigate HR response and muscle power performance.MethodsThirteen taekwondo athletes of national and international level (mean ± SD: age: 17.6 ± 2.7 years) voluntarily participated in the study. In two experimental sessions, athletes performed: the PSTT to identify HRDP and KFDP; a sport-specific IT at the KFDP, using the technical action of bandal-chagi (3 rounds × 2 min/1 min of recovery in-between). During each round of the IT, the HR was recorded to identify the HRROUND. Before and after each round of the IT, muscle power performance was assessed through three countermovement jump (CMJ) tests.ResultsHRROUND was significantly correlated with HRDP (r = 0.774–0.789; p < 0.01). During round 1, HRROUND was significantly lower (p = 0.008) than HRDP. In rounds 2 and 3, there were no difference (p = 0.067 and p = 0.653, respectively) between HRROUND and HRDP. No difference was observed between pre- and post-IT CMJ performance (p = 0.210). Post-IT CMJ performance was significantly greater (p = 0.009) than that in the interval between rounds 1 and 2.ConclusionDuring the IT rounds, expected HR responses emerged and muscle power performance was not compromised. Thus, these results support the use of PSTT-derived HRDP and KFDP as practical, sport-specific indicators for tailoring IT intensity in taekwondo athletes.